Proton-activated chloride channel 1 is essential for innate host defense against bacterial sepsis - Lucien P. Garo; Kevin Brueck; Sarah Walachowski; Archana Jayaraman; Marcel Strueve; Shuang Xu; Hulbert Yang; Matthew Helmkamp; Seung Hoan Choi; Christoph Reinhardt; Markus Bosmann (Proceedings of the National Academy of Sciences, 2026)
Bacterial sepsis remains a devastating clinical problem. Here, we describe a protective role for the recently discovered acid-sensitive, proton-activated chloride channel, PACC1 (PAC/ASOR/TMEM206), during sepsis. Initially, we found PACC1 was enriched in healthy human and mouse mononuclear phagocytes, particularly macrophages, and differentially regulated by inflammatory stimuli, suggesting PACC1 involvement in innate immunity. To further investigate, we generated de novo Pacc1 knockout ( −/− ) mice, which presented without major immunologic abnormalities at baseline. Compared to wild-type (WT), Pacc1 −/− myeloid cells showed normal phagocytic uptake of acid-insensitive Escherichia coli BioParticles , but impaired development of the acidifying phagolysosome using acid-sensitive E. coli BioParticles. Transcriptomic profiling of Pacc1 −/− macrophages revealed dysregulated phagolysosomal and cytokine networks (e.g., interferons). Because phagolysosomal bacterial clearance is essential to resolve infection, we challenged Pacc1 −/− mice with intraperitoneal gram-negative E. coli sepsis. Pacc1 −/− mice displayed increased bacterial burden, immune cell infiltration, inflammation, and lethality. In contrast, phagocytosis-independent E. coli lipopolysaccharide (LPS)-induced endotoxemia yielded comparable WT and Pacc1 −/− survival, as well as similar inflammatory responses. Finally, we engineered Pacc1 -floxed ( fl/fl ) mice crossed with a myeloid lineage Cre-deleter strain to interrogate myeloid cell–intrinsic PACC1 in vivo. Consistent with a predominate role for PACC1 during phagocytosis and bacterial clearance in these cells, LysM-Cre/Pacc1 fl/fl mice exhibited impaired E. coli sepsis survival but indifferent endotoxemia phenotypes. In conclusion, PACC1 links sterilizing phagolysosomal activity with immune networks in sepsis pathobiology.